2022
DOI: 10.1159/000528208
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on the Clinical Use of Pulse Wave Velocity in Asia

Abstract: Arterial stiffness is a progressive aging process that predicts cardiovascular disease. Pulse wave velocity (PWV) has emerged as a noninvasive, valid, and reliable measure of arterial stiffness and an independent risk predictor for adverse outcomes. However, up to now PWV measurement has mostly been used as a tool for risk prediction and has not been widely used in clincial practice. This consensus paper aims to discuss multiple PWV measurements currently available in Asia and to provide evidence-based assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…However, it has been reported that baPWV correlated well with cfPWV 36 and invasive data 24 . Additionally, the clinical values of baPWV have been shown in many clinical studies 4 , 6 , 8 . Moreover, baPWV is more suitable as a screening tool because it is simpler and more convenient to measure than cfPWV 6 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, it has been reported that baPWV correlated well with cfPWV 36 and invasive data 24 . Additionally, the clinical values of baPWV have been shown in many clinical studies 4 , 6 , 8 . Moreover, baPWV is more suitable as a screening tool because it is simpler and more convenient to measure than cfPWV 6 .…”
Section: Discussionmentioning
confidence: 96%
“…To assess multicollinearity among explanatory variables, the variance inflation factor (VIF) was introduced. Multiple binary logistic regression analyses were conducted to evaluate whether a higher baPWV (≥ 1400 cm/s), indicative of abnormal arterial stiffening 8 could predict lower HRR (< 26 beats/min, the median value). The same confounders were controlled for as those used in the multiple linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular risk and all-cause mortality, in particular, increase as much as 15% each with a 1 m/s elevation in PWV [ 5 , 10 ]. Quantification of PWV can be compromised by several common cardiovascular disease states, including AAA and peripheral arterial occlusive disease [ 11 , 12 ], so pursuance of a more reliable technique, with fewer confounding comorbidities, can amplify access to vascular stiffness measurements and potentially direct medical therapy titration in clinical scenarios known to promote stiffness, such as hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of vascular biomarkers can help to identify patients with high cardiovascular risk providing opportunity for early preventive interventions to avoid clinical endpoints like cardiovascular morbidity and mortality. Recently a consensus paper was published on the clinical use of pulse wave velocity (PWV) (Park et al, 2022) suggesting that in the near future the importance of PWV measurements in everyday clinical practice will increase (Vlachopoulos et al, 2015).…”
mentioning
confidence: 99%